PENGARUH KECOCOKAN TUGAS DAN PEMANFAATAN TEKNOLOGI SISTEM INFORMASI TERHADAP KINERJA INDIVIDUAL PADA KANTOR WILAYAH XI DIREKTORAT JENDERAL PAJAK JAWA BAGIAN TIMUR I - Sukamto, Sukamto (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2006)
Today the technology of information system in organization, both business organization and government organization become important dealing with punctuality and the true of suppying on information which are inquired by customer. However the utilization of information technology on information system an organization must be considered carefully because of the amount technology investment is relative large. The information system is one of the potential tools to create competition, because it can increase productivity (Bodnar and Hopwood, 1995). The aim of this research is to gain empirical prove which shows task-techology fit and utilization technology have positive influence to individual performance and task-techology fit has significant influence to the utilization of information technology by individual. The sample for this research is every employee at Kantor Wilayah XI Direktorat Jenderal Pajak Jawa Bagian Timur I for using information system based on computer to identify, get, integrate, implementing data on running task. The research find empirical prove which is to predict the performance effect which caused by information technology that have ti insert both task-techology fit and the utilization of information technology. The result of this research also gives empirical prove that causal relation between task-techology fit and the utilization of information technology.